The e-Tail Option - From Brick and Mortar to Wish and Click - Sultana, Nazia (Indian Journal of Marketing, 2008)
Huge population, increasing per capita income and changing consumer habits have culminated in the booming of the retail sector in India. Retail sector is expected to grow at GDP of 7% by 2010 and enlarge its market share to 280 billion from its present level of 200 billion (2007). Thanks to an expanding economy and technology orientation, consumer spending in India is expected to grow rapidly, making India’s 300 billion annual retail market to swell to 637 billion a by 2015. An email address and a website have become a necessity and not a mere accessory. e-Tailing usually comprises of online-retailers and online-auctions. As per the report released by Internet & Mobile Association of India and IMRB International, the total online transactions in India stood at Rs.7080 crore (approx 1.75 billion) for 2006-07 and is expected to grow by 30% to touch Rs.9210 crore (approx 2.15 billion) by 2001-07. e-Tailing is just not about building a pretty website loaded with beautiful pictures of your brand. It is about integrating business plan, revenue models, potential alliances, supply chain and e-Commerce initiatives. Reasons for retailers to use e-medium can be attributed to lack of real estate costs, no inventory hassles, and better interactions with customers. These are the areas where the majority of new e-biz players are scoring hits against their brick and mortar counterparts, offering the customer, as they do, new methods of buying, customizing and most importantly getting low prices. What e-tail sector is experiencing today is certainly the tip of the ice berg. Today it might be a mere Rs 12 crore industry, but its growth potential is not possible to put into figures against the industry’s size or growth. It is expected to log in as much as Rs.1000 crore in the next five years. Further fillip to e-Tailing is given with increased Internet penetration. This paper tries to present e-tailing scenario in India with future growth prospects and also identifies constraints faced in sustaining a successful e-Tail business models.